miR-16 and miR-103 impact 5-HT 4 receptor signalling and correlate with symptom profile in irritable bowel syndrome - Wohlfarth, Carolin; Mellein, Stefanie; Dweep, Harsh; Fischer, Christine; Granzow, Martin; Burwinkel, Barbara; Lorenzo Bermejo, Justo; Röth, Ralph; Lasitschka, Felix; Rappold, Gudrun; Niesler, Beate (Scientific reports, 2017)
Irritable bowel syndrome (IBS) is a gut-brain disorder involving alterations in intestinal sensitivity and motility. Serotonin 5-HT4 receptors are promising candidates in IBS pathophysiology since they regulate gut motor function and stool consistency, and targeted 5-HT4R selective drug intervention has been proven beneficial in subgroups of patients. We identified a single nucleotide polymorphism (SNP) (rs201253747) c.*61 T > C within the 5-HT4 receptor gene HTR4 to be predominantly present in diarrhoea-IBS patients (IBS-D). It affects a binding site for the miR-16 family and miR-103/miR-107 within the isoforms HTR4b/i and putatively impairs HTR4 expression. Subsequent miRNA-profiling revealed downregulation of miR-16 and miR-103 in the jejunum of IBS-D patients correlating with symptoms. In vitro assays confirmed expression regulation via three 3′UTR binding sites. The novel isoform HTR4b_2 lacking two of the three miRNA binding sites escapes miR-16/103/107 regulation in SNP carriers. We provide the first evidence that HTR4 expression is fine-tuned by miRNAs, and that this regulation is impaired either by the SNP c.*61 T > C or by diminished levels of miR-16 and miR-103 suggesting that HTR4 might be involved in the development of IBS-D.
Gesehen am 01.02.2018